Towards a multiscalar perspective on the prospects of ‘the actually existing smart village’ – a view from Hungary - Szalai, Ádám; Varró, Krisztina; Fabula, Szabolcs (Hungarian Geographical Bulletin, 2021)
This paper aims at expanding the scope of the dominantly pragmatic, local scale-oriented smart village scholarship towards a perspective that recognizes that smart village development is a multiscalar political process. To show the necessity of this move, the shaping of smart village policies and practices in Hungary is examined through a qualitative lens. As the authors argue, path-dependent structural obstacles and interscalar relations undermine the prospects of smart village building in the sense of bottom-up integrated rural development, and there is a risk of a bias towards technological innovation. This exploratory article, using Hungary as a case study, argues that smart village scholarship should draw on the results of critical smart city scholarship to acquire in-depth understanding of current debates regarding potential smart village developments.